p53: exercise capacity and metabolism - Wang, Ping-yuan (2012)
PURPOSE OF REVIEW: There is an inverse relationship between cancer incidence and cardiorespiratory fitness in large population studies. Mechanistic insights into these observations may strengthen the rationale for encouraging exercise fitness in the clinics for cancer prevention and may promote the development of new preventive strategies. RECENT FINDINGS: Studying the multi-faceted activities of p53, a critical tumor suppressor gene, has revealed various cellular pathways necessary for adapting to environmental stresses. Genetic connections are being made between p53 and an increasing number of metabolic activities such as oxidative phosphorylation, glycolysis and fatty acid oxidation. In vivo mouse models show that p53 plays an important role in determining both basal aerobic exercise capacity and its improvement by training. SUMMARY: The genetic pathways by which p53 regulates metabolism and exercise may help explain significant epidemiologic observations connecting cardiorespiratory fitness and cancer. Further understanding of these molecular pathways through human translational studies may promote the development of new cancer preventive strategies.